Does Psychopathology in Childhood Predict Internet Addiction in Male Adolescents? - Cho, Sun-Mi; Sung, Min-Je; Shin, Kyoung-Min; Lim, Ki; Shin, Yun-Mi (Child Psychiatry & Human Development, 2013)
This study investigated childhood psychopathology and Internet addiction in adolescents. Initial assessment data were obtained from 1998 to 1999, and a follow-up assessment was performed in 2006, when the original subjects entered middle school. Personal information for the 524 male subjects was obtained from the original data. The subjects were evaluated with the Korean version of the child behavior checklist, which was administered to the children's parents. Demographic and psychosocial factors were also evaluated. Children were reassessed with the self-reported Korea Internet Addiction Scale. Our results indicated that 3.6 % of the subjects had Internet addiction, and revealed a significant relationship between withdrawal and anxiety/depression and future Internet addiction. The results suggest that withdrawal and anxiety/depression during childhood should be considered in the etiology of problematic Internet use in boys. Accordingly, clinicians should consider anxiety/depression and withdrawal during childhood to prevent Internet addiction.